Investigation of Anti-inflammatory Properties of Swertia chirayta and Gloriosa superba - Satish K. Verma3, Santosh K. Singh4, Deepika Mathur5, GBKS Prasad2, V.K. Dua1, Abhishek Mathur1 (Recent Research in Science and Technology, 2011)
Gloriosa superba (Liliaceae) is one of the oldest ingredients of species from ancient time. Tubers roots and seeds are two most important part of glory lily used for variety of purpose. Swertia chirata (Gentianaceae) is widely used in India to treat fever and malaria. It is also used to treat liver diseases. The whole plant methanol and aqueous extracts of Swertia chirayta possessed maximum anti-inflammatory activity in a dose dependent manner i.e 50 mg/kg and 100 mg/kg in carrageenan induced animal models. Further screening of the potent extracts of the plant confirmed the presence of xanthone (1, 5-dihydroxy-3, 8-dimethoxy xanthone, m.p.1850C, yellowish crystalline needles from methanol) was obtained. The structure of the fraction was confirmed by spectral analysis (UV, IR, NMR). The methanol and aqueous extracts of tubers of Gloriosa superba also possessed good anti-inflammatory in a dose dependent manner i.e 100 mg/kg and 200 mg/kg in carrageenan induced animal models. Further screening of the extracts confirmed the presence of colchicines in the extracts. The present study thus revealed the presence of potent anti-inflammatory drugs in these plants.